The summer of songbirds [large type] - Harvey, Kristy Woodson (Center Point Large Print, 2023)
"Nearly thirty years ago, in the wake of a personal tragedy, June bought Camp Holly Springs and turned it into a thriving summer haven for girls. But now, June is in danger of losing the place she has sacrificed everything for, and begins to realize how much she has used the camp to avoid facing difficulties in her life. June's niece, Daphne, met her two best friends, Lanier and Mary Stuart, during a fateful summer at camp. They've all helped each other through hard things and the three are inseparable even in their thirties. But when attorney Daphne is confronted with a relationship from her past -- and a confidential issue at work becomes personal -- she is faced with an impossible choice. Lanier, meanwhile, is struggling with tough decisions of her own, and when a big secret comes to light, she finds herself at odds with her best friend . . . and risks losing the person she loves most. But in spite of their personal problems, nothing is more important to these songbirds than Camp Holly Springs."--